Benzofurazane as a New Redox Label for Electrochemical Detection of DNA: Towards Multipotential Redox Coding of DNA Bases. Issue 38 (9th August 2013) - Balintová, Jana; Plucnara, Medard; Vidláková, Pavlína; Pohl, Radek; Havran, Luděk; Fojta, Miroslav; Hocek, Michal
Abstract Benzofurazane has been attached to nucleosides and dNTPs, either directly or through an acetylene linker, as a new redox label for electrochemical analysis of nucleotide sequences. Primer extension incorporation of the benzofurazane‐modified dNTPs by polymerases has been developed for the construction of labeled oligonucleotide probes. In combination with nitrophenyl and aminophenyl labels, we have successfully developed a three‐potential coding of DNA bases and have explored the relevant electrochemical potentials. The combination of benzofurazane and nitrophenyl reducible labels has proved to be excellent for ratiometric analysis of nucleotide sequences and is suitable for bioanalytical applications.